Chapter 4: Polymers and Composites (The Effects of Cutting Parameters on Surface Texture of Hybrid Composite CFRP/AL2024) - Mohamed, Prof. Ts. Dr. Saiful Bahri; Yew, Ts. Dr.Been Seok; Musanih, Muhamad Ruzlan (Trans Tech Publications Ltd, 2016)
The use of hybrid composite materials has increased due to their special mechanical and physical properties. However, machining of these material is extremely difficult due to non-homogeneous,anisotropic and highly abrasive characteristic. The performance of machined surface quality of CFRP/AI2024 was described using two level factorial methodology. This research aims to study the interaction effects and significant factors of cutting parameters on the surface quality of CFRP/AI2024 was described using two level factorial methodology. This surface quality of CFRP/AI2024 1um and 2um. The trimming process test was performed umder dry conditions using burr tools 6mm diameter of end mills. The factors investigated were spindle speed (N), feed rate (fr) and depth of cut (dc),meanwhile profile roughness parameters(Ra) of CFRP and AI2024 were the response variables. Results show that the best estimated value of fr should be 500n mm/min to 530 mm/min, N is between 2336.042 rpm. For both responses, N is the most significant effect followed by fr and dc.